Federated States of Micronesia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper analyzes recent economic developments in the Federated States of Micronesia. Real GDP grew by a modest 1 percent in 1995, well below the average growth rate recorded during 1991-94, according to tentative estimates prepared by the IMF staff. The overall fiscal balance of the national government has registered surpluses for the past several years. Total revenue and grants have increased, mainly reflecting higher nontax revenue from fishing license fees from Korea and Taiwan, Province of China, and higher non-Compact grants.